An examination of task performance fraud risk assessment on forensic accountant knowledge and mindset in Nigerian public sector - Popoola, Oluwatoyin Muse Johnson; Che Ahmad, Ayoib; Samsudin, Rose Shamsiah; Ahmad, Hartini (Asia-Pacific Education and Research Association New York, NY10128, 2013)
This paper examines task performance fraud risk assessment and forensic accountant knowledge and mindset in the Nigerian public sector. The aim of the study is to investigate the fraud risk assessment in the Nigerian public sector through the efficient exploit of forensic accountant knowledge and mindset. The effect will enhance the corporate governance and accountability practices among public sector accountants and auditors in Nigeria.